Antecedent Value of Professional Commitment and Job Involvement in Determining Job Satisfaction. (May 2016) - Deepak,
The study attempts to explore the relationship between job satisfaction of veterinarians and their level of professional commitment and job involvement. The universe of the study has been confined to veterinary doctors working on a permanent basis in government institutions in the state of Punjab. A sample of 322 veterinary doctors was collected to represent the universe. The analysis reveals that professional commitment and job involvement have positive relationship with and have explanatory power for job satisfaction. Taking into consideration the significance of animal husbandry to the growth of Indian economy and specifically to the Punjab economy, the government should take consistent and steadfast measures to improve the level of job involvement, professional commitment and, hence, job satisfaction of veterinarians. Such measures will definitely benefit the veterinarians, the government itself and the nation as a whole.